Development of molecular medicine approaches for neuromuscular disease - Hanson, B (2021)
Neuromuscular diseases are a broad group of debilitating disorders that impair muscle functioning. Duchenne muscular dystrophy (DMD) is the most common hereditary form of neuromuscular disease, for which there is currently no cure. DMD is caused by null mutations in the dystrophin gene (DMD), which encodes an essential cytoskeletal protein required for myofibre integrity and function. The leading DMD therapeutic strategy is antisense oligonucleotide-mediated ‘exon skipping’, however, this requires lifelong repeat administration. Single intervention strategies for the permanent correction of disease-causing mutations in the genomic DNA (such as CRISPR/Cas9, clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9) are important avenues for DMD therapeutic development. An AAV9-delivered CRISPR/Cas9 system was employed to excise a disease-causing Dmd exon in the severely affected double knockout (dKO) mouse (lacking dystrophin and its developmental paralogue, utrophin). Dystrophin protein expression was partially restored in the muscle of dKO mice, although no extension in lifespan was observed. Within-fibre patchiness of dystrophin expression was observed in longitudinal skeletal muscle sections, an as of yet unreported consequence of CRISPR-mediated Dmd gene editing in myofibres. This provides an insight into the myonuclear domain structure of dystrophic fibres, and raises concerns about the possible functionality of gene edited myofibres that contain interspersed dystrophin-positive and -negative regions.